Pengaruh Keragaman Produk, Persepsi Harga, Dan Fasilitas Terhadap Keputusan Pembelian : (Survei Pada Konsumen Toserba Griya Ciawi Tasikmalaya) - Dinan Hanipa Isdayanti (CV. ULIL ALBAB CORP, 2022)
This study aims to determine the influence of product diversity, price perception, and facilities on purchase decision at department store Griya Ciawi Tasikmalaya. The method used in this study is a survey method with a causal research design. With a research sample of 100 consumers department store Griya Ciawi Tasikmalaya. The results of the study show that partially product diversity has no significant effect on purchasing decisions. The price perception has no significant influence on purchasing decisions. Facilities had a significant influence on purchasing decisions. Simultaneously product diversity, price perception, and facilities have a significant influence on purchasing decisions at department store Griya Ciawi Tasikmalaya.